PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII2 SMPN 9 PEKANBARU - Fitria, Nurul; Saragih, Sehatta; ', Suhermi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak: The background of this research is not optimal results VIII2 grade students' mathematics learning SMPN 9 Pekanbaru with the percentage of students who reached the KKM is 50%. Facts on the ground showed not achieving the KKM is related to the learning process that students have not been optimally engage in learning activities. In connection with this, the researchers to improve the learning process in order to improve student learning outcomes through a research. It is expected with the implementation of this study, the learning process students become better so that students are engaged in an optimal learning and increase student learning outcomes. The Subjects were students of SMPN 9 Pekanbaru VIII2 grade total of 36 students with academic ability level heterogeneous. Instruments collecting research data is observation sheet activities of teachers and students and math achievement test in the form of daily tests. The observation of the teacher and student activity was analyzed as a basis for reflection and see the improvement of the learning process is carried out. While the achievement test used to determine students' mathematics learning outcomes. Based on the analysis of research data, there is improvement of learning process where the student has begun to actively ask and motivated to engage actively in the learning process and learning outcomes of students increased mathematics obtained. KKM achievement was 50% prior to the action and increased to 52.78% in the first cycle and became 83.33% in the second cycle. Based on these results it can be concluded that the application of the structural approach to learning model Numbered Heads Together (NHT) can improve learning outcomes VIII2 grade math student of SMPN 9 Pekanbaru even semester 2015/2016.Kata kunci: Hasil Belajar Matematika, Pembelajaran Kooperatif Pendekatan Struktural Numbered Heads Together (NHT), Penelitian Tindakan Kelas.